In vitro anti-HIV, cytotoxicity and nutritional analysis of Trianthema portulacastrum L. (Aizoaceae) - Mahboob Adekilekun Jimoh; Muhali Olaide Jimoh; Mujidat Bello; Idris Olawale Raimi; Gideon Olarewaju Okunlola; Nompumelelo Mkhwanazi; Charles Petrus Laubscher (BMC, 2024)
Abstract The development of antiretroviral therapy has brought a tremendous relief to the world as it minimizes mortality, reduces HIV transmission, and suppresses progression in infected patients. However, the orthodox antiretroviral therapy is faced with limitations which have necessitated a continuous search for more novel plant-based antiviral compounds, which can bypass the existing barriers created by drug resistance and target more viral proteins. Despite the edibility and enormous pharmacological benefits of T. portulacastrum, little is known about its nutrient profiles and potential use as a natural source of antiviral drug. This study focuses on the full feed analysis and anti-HIV potential of two biotypes of T. portulacastrum. Ethanolic extracts of both biotypes of T. portulacastrum (T01 and T02) had significant inhibitory effects on the level of replication of the HIV-1. Both extracts induced the inhibition of at least 50% of the HIV-1 viral load at considerably low IC50 values of 1.757 mg/mL (T01) and 1.205 mg/mL (T02) which is comparable to the AZT standard. The protein composition ranged between 8.63-22.69%; fat (1.84-4.33%); moisture (7.89-9.04%); fibre (23.84-49.98%); and carbohydrate content (38.54-70.14%). Mineral contents of tested T. portulacastrum varied considerably in different parts of the plant. Nitrogen N mineral ranged between 13.8-36.3 mg/g; sodium Na (2.0-14.0 mg/g); potassium K (14.0-82.0 mg/g); magnesium Mg (2.8-7.1 mg/g); calcium Ca (9.1-24.7 mg/g); phosphorus P (1.3-3.6 mg/g); iron Fe (193.5-984.0 ppm); zinc Zn (42.5-96.0 ppm); manganese Mn (28.5-167.5 ppm); and copper Cu (2.0-8.5 ppm). These mineral values are comparable or higher than values quoted for common vegetables, suggesting that T. portulacastrum is a nutrient-dense vegetable that could provide alternative sources of antiviral nutrients to HIV-infected individuals. Further studies are recommended to unravel key metabolites responsible for high nutrient profiles and antiretroviral effects in T. portulacastrum.